Gabriel's gift - Kureishi, Hanif; Faber and faber (London : Faber and faber, 2001)
A fanciful, artistic teenaged boy named Gabriel hopes for a reconciliation in his damaged family after meeting his absent father's rich and famous former band mate.
Adult
Keywords: Family -- Fiction; Parent and child -- Fiction; Teenage boys -- Fiction; Boys -- Fiction; Domestic fiction; Family life -- Fiction; Parent-child relationship -- Fiction; Teenagers -- Fiction; England -- Fiction